Islamic law of contract is getting momentum - Jalil, Md. Abdul; Rahman, Muhammad Khalilur (Centre for Promoting Ideas, 2010)
This article is basically a book review on the book written by Razali, Siti Salwani. The title of the book is the ‘Islamic Law of Contract’ which has been published by Cengage Learning from the United States in 2010. The ISBN of the book is 13: 978-981-4253-97-0 and there are a total of 124 pages. The authors of this review article (Dr. Jalil and Mr. Khalil) have reviewed the book to find its merits and demerits and finally have given some suggestions for its further improvement. The authors have also written some points on the Islamic law of contract which they think necessary for the readers (who are not exposed to the Islamic law of contract) to understand better on the Islamic law of contract as well as for a better insight on the relevant legal points involved therein.